2005
DOI: 10.1158/0008-5472.can-04-4229
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Genome-Wide Mapping of Genetic Alterations in Human Glial Brain Tumors

Abstract: High-resolution genome-wide mapping of exact boundaries of chromosomal alterations should facilitate the localization and identification of genes involved in gliomagenesis and may characterize genetic subgroups of glial brain tumors. We have done such mapping using cDNA microarray-based comparative genomic hybridization technology to profile copy number alterations across 42,000 mapped human cDNA clones, in a series of 54 gliomas of varying histogenesis and tumor grade. This gene-by-gene approach permitted the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
135
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 150 publications
(140 citation statements)
references
References 35 publications
5
135
0
Order By: Relevance
“…Clinical examinations have revealed that Mnk1 is significantly elevated in human glioma tissues (18). Several studies have shown that the potent Mnk inhibitor CGP57380 suppresses human cancer cell growth in vitro (31,(37)(38)(39), but it remains unclear whether this inhibition is due to effects on Mnk1/2 or on Mnk1/2 plus other kinases promoting cell growth (40,41).…”
Section: Mnk1/mnk2 Double Deficiency Does Not Affect Cellular Responsmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical examinations have revealed that Mnk1 is significantly elevated in human glioma tissues (18). Several studies have shown that the potent Mnk inhibitor CGP57380 suppresses human cancer cell growth in vitro (31,(37)(38)(39), but it remains unclear whether this inhibition is due to effects on Mnk1/2 or on Mnk1/2 plus other kinases promoting cell growth (40,41).…”
Section: Mnk1/mnk2 Double Deficiency Does Not Affect Cellular Responsmentioning
confidence: 99%
“…Enhanced eIF4E phosphorylation has been observed in various solid tumors (13) and lymphomas (14) and correlates with poor patient prognosis, particularly in non-smallcell lung cancer (15). Furthermore, Mnk1 is highly expressed in hematological malignancies (16,17), and both Mnk1 and Mnk2 are up-regulated in solid tumors such as gliomas and ovarian cancers (18,19). Consistent with these clinical findings, in vitro studies have shown that NIH 3T3 cells expressing phosphodefective eIF4E display diminished transformation activity, whereas overexpression of wild-type (WT) eIF4E fully transforms this cell line (20,21).…”
mentioning
confidence: 99%
“…Their result indicated that 15q23-q26.3 harbors a novel susceptibility allele for familial glioma, and since their finding, improved higher resolution molecular genetic technology has marked the progress of mapping genetic changes in PBTs. Bredel et al 27 conducted a high-resolution mapping by using cDNA microarray CGH technology to profile genetic changes with 42,000 cDNA clones in a cohort of 54 glioma patients and identified five novel minimally deleted loci thought to be important in gliomagenesis. The study successfully predicted astrocytoma and oligodendroglioma with 92% and 88% accuracy, respectively, based on 170 gene copy number patterns.…”
Section: Cytogenetic Markers Used For Molecular Epidemiology In Pbtsmentioning
confidence: 99%
“…The website is powered by an Apache server. Blaveri et al (2005) 92.9 Bredel et al (2005) 91.7 Gysin et al (2005) 92.6 Janoueix- Lerosey et al (2005) 97.4 Mosse et al (2005) 61.7 Patil et al (2005) 92.8 Snijders et al (2005) 93.2 de Leeuw et al (2004) 71.5 Douglas et al (2004) 99.3 Nakao et al (2004) 93.0 Woodfine et al (2004) 99.8 Veltman et al (2003) 74.2 Chen et al (2002) 83.8 Pollack et al (2002) 88.5 Snijders et al (2001) 89 …”
Section: Hardware Requirements and Implementationmentioning
confidence: 99%
“…Many studies have been carried out on bladder cancer (Veltman et al, 2003;Blaveri et al, 2005;Stransky et al, 2006), brain cancer (Bredel et al, 2005;Kotliarov et al, 2006), breast cancer (Pollack et al, 2002;Fridlyand et al, 2006), colon cancer (Douglas et al, 2004;Nakao et al, 2004), liver cancer (Patil et al, 2005), lymphoma (de Leeuw et al, 2004), neuroblastoma (JanoueixLerosey et al, 2005;Mosse et al, 2005), mouth cancer (Snijders et al, 2005), pancreas cancer (Gysin et al, 2005) and replication timing (Woodfine et al, 2004;Janoueix-Lerosey et al, 2005). Comparisons of the results of experiments from different laboratories, on different types of cancer, are required to validate results or hypotheses and to improve our understanding of the recurrent alterations involved in cancer.…”
Section: Introductionmentioning
confidence: 99%